Laplace Adomian Decomposition Method for Fractional Order SIS Epidemic Model - Amera Shaiab, (AlQalam Journal of Medical and Applied Sciences, 2024)
This research manuscript addresses finding a solution to the SIS Epidemic model using the Caputo derivative. To achieve the required results, Laplace transform together with the Adomian Decomposition Method (LADM) were utilized. This method is a powerful tool for dealing with various linear and nonlinear problems of fractional-order differential equations (FODEs). Additionally, some results related to the qualitative theory of the model of interest were studied. The computational results showed the verification of the performed analysis. The investigation of the approximate solution computed in the form of an infinite series was carried out. The results were graphically displayed to analyze the adopted procedure for solving nonlinear FODEs using the Caputo fractional derivative. تتناول هذه الورقة البحثية إيجاد حل لنموذج "عرضة للإصابة - مصاب - عرضة" للإصابة الوبائي باستخدام مشتقة كابوتو. لتحقيق النتائج المطلوبة، تم استخدام تحويل لابلاس مع طريقة تحلل أدوميان. تُعتبر هذه الطريقة أداة قوية للتعامل مع المشكلات الخطية وغير الخطية المختلفة للمعادلات التفاضلية الكسرية الرتبة (FODEs). بالإضافة إلى ذلك، تم دراسة بعض النتائج المتعلقة بالنظرية النوعية للنموذج محل الاهتمام. تم التحقيق في الحل التقريبي المحسوب في شكل سلسلة لانهائية. تم عرض النتائج بشكل بياني لتحليل الإجراءات المعتمدة لحل المعادلات التفاضلية الكسرية غير الخطية باستخدام مشتقة كابوتو الكسرية.